2016
DOI: 10.1093/jrr/rrw120
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose or low-dose-rate ionizing radiation–induced bioeffects in animal models

Abstract: Animal experimental studies indicate that acute or chronic low-dose ionizing radiation (LDIR) (≤100 mSv) or low-dose-rate ionizing radiation (LDRIR) (<6 mSv/h) exposures may be harmful. It induces genetic and epigenetic changes and is associated with a range of physiological disturbances that includes altered immune system, abnormal brain development with resultant cognitive impairment, cataractogenesis, abnormal embryonic development, circulatory diseases, weight gain, premature menopause in female animals, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
85
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 134 publications
1
85
0
3
Order By: Relevance
“…The considerable variation in elevation throughout the FEZ therefore appears to be a modulating factor for most species' response to human presence. Although we did not capture animals to quantify any potential biological effects resulting from radiation exposure, detection of radiation effects at the molecular level would be expected in many animals within the study area, based on the ambient dose rates in which they were living (see review of low-dose rate effects in Tang et al [2016]). Other researchers have documented radiation effects on wildlife exposed to the fallout from Fukushima, including DNA damage (in earthworms [Megascolecidae spp ;Fujita et al 2014], wild boar [Fujita et al 2014 Murase et al 2015]).…”
Section: Discussionmentioning
confidence: 99%
“…The considerable variation in elevation throughout the FEZ therefore appears to be a modulating factor for most species' response to human presence. Although we did not capture animals to quantify any potential biological effects resulting from radiation exposure, detection of radiation effects at the molecular level would be expected in many animals within the study area, based on the ambient dose rates in which they were living (see review of low-dose rate effects in Tang et al [2016]). Other researchers have documented radiation effects on wildlife exposed to the fallout from Fukushima, including DNA damage (in earthworms [Megascolecidae spp ;Fujita et al 2014], wild boar [Fujita et al 2014 Murase et al 2015]).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the repair capacity of mtDNA is tissue-specific, with characteristics such as high sensitivity to oxidative stress, slower repair and faster accumulation of oxidative damage observed in mice brains compared with other tissues (testis, kidney and liver) (Karahalil et al 2002) indicating that the mitochondria in brain tissue could be particularly sensitive to exposure to environment stress. Indeed, brain development is affected by exposure to elevated levels of radiation: prenatal exposure to ionizing radiation is associated with impaired neurogenesis (Tang et al 2017), as well as reduced brain size in laboratory mice (Verreet et al 2016), and also in birds (Møller et al 2011) and bank voles (Kivisaari et al unpublished) inhabiting contaminated areas in the Chernobyl region.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Great Britain showed that people who had low birth weight were at increased risk of coronary heart disease and the disorders related to it [18]. Animal and human studies have shown that the LBW proportions (LBWp) increase with toxic exposure and with radiation exposure [19][20][21]. Smoking increases the LBWp in a dose-dependent manner [22], possibly due to elevated radionuclides in tabaco [23].…”
Section: Introductionmentioning
confidence: 99%